2021
DOI: 10.3390/ijerph18116158
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Depression Associated with Chewing Problems in the Korean Elderly Population

Abstract: Unlike younger adults, depression in older adults is sometimes related to chewing problems. This study examined the risk factors related to depression associated with chewing problems in 3747 elderly individuals using the Korean National Health and Nutrition Examination Survey. Approximately 41.2% of the total subjects reported chewing problems. There were significant differences in age, education, marital status, individual income, current smoking status, and aerobic physical activity in relation to chewing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…If dentures were used, the subjects were asked to answer while wearing their dentures. Subjects were divided into "chewing difficulty (CD)" for "very uncomfortable" and "uncomfortable" and "no chewing (NCD)" for "moderate", "not uncomfortable", and "not at all uncomfortable" according to the question of mastication discomfort [20].…”
Section: Measurements 221 Chewing Statusmentioning
confidence: 99%
“…If dentures were used, the subjects were asked to answer while wearing their dentures. Subjects were divided into "chewing difficulty (CD)" for "very uncomfortable" and "uncomfortable" and "no chewing (NCD)" for "moderate", "not uncomfortable", and "not at all uncomfortable" according to the question of mastication discomfort [20].…”
Section: Measurements 221 Chewing Statusmentioning
confidence: 99%
“…16 Previous studies suggested older adults who have poor chewing ability are more prone to experience insufficient nutrient intake, 17 impaired cognition, 18 and depression. 19 In addition, few community-based surveys reported chewing ability was associated with frailty. Namely, older adults with chewing difficulty or poor chewing ability were more prone to experience frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Chewing ability refers to individuals' masticatory performance in chewing selected common foods 16 . Previous studies suggested older adults who have poor chewing ability are more prone to experience insufficient nutrient intake, 17 impaired cognition, 18 and depression 19 . In addition, few community‐based surveys reported chewing ability was associated with frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that these individuals at risk have a 20% higher probability of requiring acute hospital care and a 60% higher mortality rate (6). Therefore, adequate nutrition is one of the requirements of independent living and malnutrition is an important factor affecting mortality and morbidity (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Depression creates reluctance, physical weakness, and loss of appetite; dementia on the other hand may lead to malnutrition due to reasons such as not feeling hungry as a result of brain atrophy, eating behavior disorder, and difficulty in swallowing (12)(13)(14)(15). As a result, all these changes affect each other negatively and bring along many problems such as a decrease in life expectancy, the need for care from others, and an increase in the burden on health services (8).…”
Section: Introductionmentioning
confidence: 99%